Uji Akivitas Imunomodulator Ekstrak Buah Petai (Parkia speciosa Hassk.) terhadap Titer Imunoglobulin (IgG) pada Mencit Balb/c yang Diinduksi dengan SDMD - Yithro Serang; Ferika Indrasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Immunomodulators are substances or drugs that can modulate the function and activity of the immune system. Most of the medicinal plants that have been studied prove the presence of immunostimulators, while immunosuppressors are still rare. Petai plants can function as antioxidants. There is a close relationship between antioxidants and the immune system giving antioxidants can stimulate and protect the cellular immune system. The purpose of this study was to determine the effect of administration and effective dose of petai fruit (Parkia speciosa Hassk) ethanol extract on increasing IgG titer in Balb / c mice induced by SDMD.This research method was started with Petai extraction and then tested for chemical content. Experimental animals consisted of 25 mice divided into 5 treatment groups, each group consisting of 5 mice. All groups were immunized with 1% SDMD as much as 0.2 ml / 20 g BB on day 8 (after being acclimatized for 7 days) intravenously. Test preparation is given orally for 7 days. On day 14, blood collection from retro orbital plexus was performed to collect serum and examined immunoglobulin G titers with indirect ELISA method.The benefit to be obtained from this study is to prove the ethanol extract of petai fruit (Parkia speciosa Hassk) can increase the immune system against foreign compounds with an increase in IgG titer in Balb / c mice induced by HRD. The results of Petai Fruit Extract Dosage 4.125 mg / KgBB, 8.25 mg / Kg BB and a dose of 16.5 mg / Kg BB give an effect on increasing IgG titers. The dose of 16.5 mg is better than stimouno in increasing IgG levels of mice induced by HRD.Keywords— Petai (Parkia speciosa Hassk), IgG, SDMD,ELISA